Common fixed points for suzuki-generalized nonexpansive maps - Maryam A. Alghamdi (2018)
A common fixed point theorem for a pair of maps satisfying condition (C) is proved under certain conditions. We extend the well-knownDeMarr's fixed point theorem to the case of noncommuting family of maps satisfying condition (C). As for an application, an invariant approximation theorem is also derived. © 2013 Maryam A. Alghamdi et al.